2017
DOI: 10.3892/or.2017.5642
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the YAP1 oncogene in clear cell renal cell carcinoma is associated with poor outcome

Abstract: Abstract. Clear cell renal cell carcinoma (ccRCC) is the most common subtype of RCC (70-80%). Yes-associated protein 1 (YAP1) protein is a nuclear effector of the Hippo pathway and acts as a transcriptional co-activator of genes involved in the processes of growth and development of tissues. Hippo signaling, with its key kinases, MST2 and large tumor suppressor kinase 1 (LATS1), plays a significant role in the negative regulation of the amount and activity of YAP1 protein. Components of the Hippo pathway and Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 67 publications
(98 reference statements)
5
40
0
Order By: Relevance
“…In an immunohistochemical study lower LATS1 protein expression was found in renal cancer tissue and it correlated with the clinical stage and pathological grade of ccRCC [ 29 ]. Decreased level of LATS1 immunoreactivity in ccRCC cells, as observed in the present study, corresponds to the analysis of LATS1 gene expression on another set of ccRCC patients where we observed strong association between decreased LATS1 mRNA and protein contents in cancer tissue lysates [ 13 ]. We also identified the possible epigenetic mechanism of decreased LATS1 level: the hypermethylation of LATS1 promoter region was strongly associated with lower LATS1 content [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In an immunohistochemical study lower LATS1 protein expression was found in renal cancer tissue and it correlated with the clinical stage and pathological grade of ccRCC [ 29 ]. Decreased level of LATS1 immunoreactivity in ccRCC cells, as observed in the present study, corresponds to the analysis of LATS1 gene expression on another set of ccRCC patients where we observed strong association between decreased LATS1 mRNA and protein contents in cancer tissue lysates [ 13 ]. We also identified the possible epigenetic mechanism of decreased LATS1 level: the hypermethylation of LATS1 promoter region was strongly associated with lower LATS1 content [ 13 ].…”
Section: Discussionsupporting
confidence: 89%
“…These observations are in concordance with our previously performed analysis of the YAP1 expression at the mRNA and protein levels by QPCR and Western blotting techniques, respectively. In that study we showed that YAP1 gene upregulation and worse clinical outcome of ccRCC patients as well as higher YAP1 protein expression in cancer tissue homogenates were associated with the clinical stage and pathomorphological features such as higher TNM and Fuhrman's stages [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histological staining of tumors and experiments in cancer cell lines have implicated YAP/TAZ in several other solid tumor types, including ovarian, [ 120–127 ] prostate, [ 128–134 ] bladder, [ 135–139 ] endometrial, [ 140,141 ] kidney, [ 142–144 ] thyroid, [ 145–149 ] adrenal, [ 150 ] mesothelioma, [ 151,152 ] sarcomas, [ 153–156 ] and epithelioid hemangioendothelioma. [ 157,158 ] In all the above cases, genetically engineered mouse models are still necessary to establish the causative role of Yap/Taz in these tumors in vivo.…”
Section: Introductionmentioning
confidence: 99%